D2-Hydroxyglutaric Aciduria Type II with Subdural Hemorrhage Identified in a 3-Month-Old Infant: A Case Report - Green, Jennie; Rao, Vinod; Currie, Melissa (Journal of Pediatric Neurology, 2020)
Subdural hemorrhage in association with D2-hydroxyglutaric aciduria (D2-HGA) Type II has only been described once in the medical literature in a 15-month-old child (1). Our case report describes a much younger 3-month-old infant previously diagnosed with D2-HGA Type II, who presented clinically with seizures and identified to have bilateral subdural hematomas concerning for possible physical abuse. This case report discusses the genetic diagnosis of D2-HGA and interpretation of subdural hemorrhage in context of evaluating possible physical abuse concerns. When an underlying medical condition is known to be present and a child presents with findings that may be concerning for physical abuse, it is critical to consider the possibility that the underlying medical condition may contribute to or may be the cause of the findings.
Keywords: subdural hemorrhage; glutaric aciduria; child abuse mimic